2015
DOI: 10.1063/1.4927221
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal asphaltene deposition in laminar pipe flow: Flow rate and parametric effects

Abstract: Deposition from a suspended phase onto a surface can aversely affect everyday transport processes on a variety of scales, from mineral scale corrosion of household plumbing systems to asphaltene deposition in large-scale pipelines in the petroleum industry. While petroleum may be a single fluid phase under reservoir conditions, depressurization upon production often induces a phase transition in the fluid, resulting in the precipitation of asphaltene material which readily aggregates to the colloidal scale and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…It has been suggested that the rate of deposition of sub-micron aggregates is mass-transport limited, depending on the diffusivity and thus the size of depositing particles [24,56]. In deposition models the main factors governing deposition rate are the number of destabilized particles, the size of destabilized particles (which governs their diffusivity and transport through the liquid), the flow conditions (hydrodynamics) and other environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the rate of deposition of sub-micron aggregates is mass-transport limited, depending on the diffusivity and thus the size of depositing particles [24,56]. In deposition models the main factors governing deposition rate are the number of destabilized particles, the size of destabilized particles (which governs their diffusivity and transport through the liquid), the flow conditions (hydrodynamics) and other environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Numerous studies have examined the arterial deposition of asphaltenes in glass and stainless steel capillary pipes. 7,[10][11][12][13][14][15][16] Diffusion is typically assumed to be an important mechanism leading to asphaltenes deposition. Nabzar et al proposed a colloidal model for asphaltene deposition in the diffusion-limited and shear-limited regimes.…”
Section: Introductionmentioning
confidence: 99%
“…A few case studies were performed to measure the thickness of the deposited layer in well tubing with diameters of 4.5 and 1.75 in. (Haskett and Tartera 1965;Al-Kafeef et al 2005). In one case, asphaltene deposition in a west Kuwait well was assessed through measurements of flowing wellhead pressure by a pressure gauge, and found to reach one-third of the inner well-tubing radius (Al-Kafeef et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In one case, asphaltene deposition in a west Kuwait well was assessed through measurements of flowing wellhead pressure by a pressure gauge, and found to reach one-third of the inner well-tubing radius (Al-Kafeef et al 2005). In another case, with a similar method, the deposit in five different wells of the Hassi Messaoud field in Algeria was measured, and found to reach approximately two-thirds of the inner-tubing radius (Haskett and Tartera 1965). Such excessive deposition greatly reduces production efficiency.…”
Section: Introductionmentioning
confidence: 99%